Evaluasi Peraturan Daerah Surabaya Nomor 3 Tahun 2018 : (Studi Kasus : Jalan Tunjungan dan Kota Lama) - Qurnia Annashrida; Supri Hartono; Hasan Ismail (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This research aims to evaluate Surabaya City Regional Regulation Number 3 of 2018 concerning Transportation Implementation in an effort to curb illegal parking in Surabaya City. The background of this research is based on the rampant practice of illegal parking even though the policy has been enacted several years ago and various efforts have been made by the City Government. This research uses a descriptive qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model. Data collection techniques were conducted through observation and in-depth interviews with Transportation Department officers, parking attendants, and parking users in the area of Jalan Tunjungan and Kota Lama Surabaya. The results showed that this policy has a strong legal foundation and institutional structure as well as cross-sector coordination efforts. However, its implementation is still constrained by limited human resources, low public participation, weak supervision and enforcement of sanctions, and not optimal periodic policy evaluation. The implication of this finding shows the need for improvement in technical implementation in the field as well as the importance of evaluating and updating policies so that illegal parking control policies can run more effectively and have a real impact on traffic order in Surabaya City.